Integrity of Sperm Cell Bali Bull Preserved at 5°C Using a Diluent Formulation of Extracted Red Fruit and Coconut Water - Ervandi, M. (Journal La Lifesci, 2023)
This study aims to determine the role of the best diluent in protecting the integrity of the spermatozoa membrane after storage using an alternative diluent formulation of red fruit extract (Pandanus Conoideus Lamk) and coconut water. An alternative diluent formulation featuring red fruit extract (Pandanus Conoideus Lamk) and coconut water was utilized. Fresh semen from Bali Bull was evaluated in the Integrated Field Laboratory, Department of Animal Science of Universitas Muhammadiyah Gorontalo. Bali bull sperm of high quality was diluted using a combination diluent containing red fruit extract (Pandanus Conoideus Lamk), green coconut water, and CEP-2 mixed with 10% egg yolk. Technical term abbreviations were explained at their initial use. Spermatozoa membrane integrity was assessed using the hypoosmotic swelling test (HOST), while chlortetracycline (CTC) fluorescent dye was used to evaluate spermatozoa capacitation and acrosome reaction. The randomized group design (RAK) was used in the research, consisting of four conditions and 10 replications. P0 served as the control group, which received CEP-2 plus 10% egg yolk. P1 was administered EBM diluent AK enriched with 15% KT, while P2 received EBM diluent AK plus 15% KT and fructose 1 mg/ml. P3 was given EBM diluent AK plus 15% KT and fructose 2 mg/ml. Analysis of variance was used to examine the resulting data. The findings indicated that CEP-2 plus 10% egg yolk diluent was more effective than the diluent formulations containing red fruit extract and coconut water. Spermatozoa with intact membranes and no capacitation remain high, while those with capacitation and acrosome reaction remain low.